Vitamin D Status and Its Correlation With Anthropometric and Biochemical Indicators of Cardiometabolic Risk in Serbian Underground Coal Miners in 2016 - Šarac, Ivana; Jovanović, Jovica; Zec, Manja; Pavlović, Zoran; Debeljak-Martačić, Jasmina; Zeković, Milica; Milešević, Jelena; Gurinović, Mirjana; Glibetić, Maria (Frontiers in Nutrition, 2021)
The status of vitamin D (VitD) in underground working coal miners is rarely studied, as well as its association with their cardiometabolic health. The aim was to examine VitD status in Serbian underground coal miners and to correlate it with anthropometric and laboratory indicators of cardiometabolic risk. Nutritional data (food frequency questionnaire-FFQ and twice repeated 24h-recall), anthropometric data (including segmental analysis by bio-impedance analyzer TANITA BC-545N), arterial tension and biochemical and hematological data of 103 coal miners (aged 22–63 years) were correlated with their late summer (early September) serum 25(OH)D levels (measured by HPLC). 68.9% of the studied coal miners were overweight /obese, and 48.5% had metabolic syndrome. The mean VitD nutritional intakes were low: 5.3±3.8 μg/day (FFQ) and 4.9±8.0 μg/day (24h-recalls), but the mean serum 25(OH)D levels were surprisingly high (143.7±41.4 nmol/L). Only 2.9% of coal miners had 25(OH)D levels lower than 75 nmol/L (indicating insufficient/deficient status), while 63.2% had values above 125 nmol/L (upper optimal limit), and even 10.7% had values above 200 nmol/L. There was no statistical difference in 25(OH)D levels in coal miners with or without metabolic syndrome (or overweight/obesity). Interestingly, 25(OH)D levels were in significant positive correlations with body mass index (BMI), fat mass (FM), fat mass percentage (FM%), limbs FM%, serum triglycerides, GGT, AST, ALT, ALT/AST ratio, and in significant negative correlations with serum HDL-cholesterol and age. All these correlations were lost after corrections for age, FM, FM%, and legs FM%. In Serbian coal miners, high levels of early-September VitD levels were observed, indicating sufficient non-working hours’ sun-exposure during summer period. Furthermore, the unexpected positive correlations of VitD levels with anthropometric and biochemical parameters indicative for obesity, metabolic syndrome and fatty liver disease were found. More research is needed on VitD status of coal miners (particularly in winter period), and its relationship with their cardiometabolic status.